Evaluation of garlic, BAU-biofungicide, bion and chemical fungicides in controlling leaf spot of Taro - Sohag, MAS; Hossen, MT; Monjil, MS (Progressive Agriculture, 2017)
The field experiment was conducted to evaluate the efficacy of Garlic extract @ 10%, BAU-Biofungicide @ 2%, Bion@ 0.2%, Bavistin DF (Carbendazim) @ 0.1% and Proud 250EC (Propiconazole) @ 0.1% for controlling leaf spot disease of taro (Colocasia esculenta). Performance of these treatments was assessed by applying as cormel treatment and foliar spray. Cormel treatment under field experiment was found effective for BAU-Biofungicide and Proud 250EC. Bavistin DF and Proud 250EC was more effective than other treatments in increasing plant height and healthy leaves, and in decreasing spotted and dead leaves. Before foliar spraying, BAU-Biofungicide as cormel treatment reduced the disease incidence (46.19%) and severity (25.28%) of taro leaf spot at 180 days after sowing. As foliar spray all the treatments has significant effect on taro leaf spot. Among the treatments BAU-Biofungicide was found superior to control leaf spot of taro. BAU-Biofungicide resulted maximum reduction of disease incidence and severity and increase in number of healthy leaf followed by Bion and Proud 250EC. BAU-Biofungicide showed enhanced results in terms of disease incidence and severity of leaf spot of Taro before and after foliar spraying. Progressive Agriculture 28 (3): 167--173, 2017